2020
DOI: 10.1016/j.eclinm.2020.100548
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin for primary prevention of ST segment elevation myocardial infarction in persons with diabetes and multiple risk factors

Abstract: Background Controversy exists as to whether low-dose aspirin use may give benefit in primary prevention of cardiovascular (CV) events. We hypothesized that the benefits of aspirin are underevaluated. Methods We investigated 12,123 Caucasian patients presenting to hospital with acute coronary syndromes as first manifestation of CV disease from 2010 to 2019 in the ISACS-TC multicenter registry (ClinicalTrials.gov, NCT01218776). Individual risk of ST segment elevation myoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…But early percutaneous coronary intervention (PCI) is the main treatment method in STEMI patients [30] . A number of studies have found that STEMI patients have a higher risk of short-term or long-term adverse events than NSTEMI patients [31] , [32] , [33] . Therefore, we used the five methods to describe the MI subtypes, including disease phase, lesion range, infarction location, ECG expression and clinical type in the first version of MIRKB.…”
Section: Discussionmentioning
confidence: 99%
“…But early percutaneous coronary intervention (PCI) is the main treatment method in STEMI patients [30] . A number of studies have found that STEMI patients have a higher risk of short-term or long-term adverse events than NSTEMI patients [31] , [32] , [33] . Therefore, we used the five methods to describe the MI subtypes, including disease phase, lesion range, infarction location, ECG expression and clinical type in the first version of MIRKB.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical trials, elevated CV risks appear to be class-specific to selective COX-2 inhibitors with increased COX-2 specificity, higher dose, and longer duration increasing the AE risk exposure [ 21 , 29 32 ]. Many NSAIDS (e.g., ibuprofen, diclofenac, naproxen, and celecoxib) increase the risk of heart failure by approximately two-fold, linked in part to the renal COX-2-mediated effects on BP and sodium retention [ 22 , 32 ].…”
Section: History Of Safety Concerns Of Cox-2 Inhibitors and Nonselect...mentioning
confidence: 99%
“…5 Aspirin intervention is one of the most effective and immediate medication of patients with STEMI. 6 The standard guidelines recommend that aspirin 300 mg be given orally as soon as possible by emergency medical personnel. 7 As a result, pre-hospital aspirin use has been found to improve the outcome of STEMI and is considered safe.…”
Section: Introductionmentioning
confidence: 99%
“…7 As a result, pre-hospital aspirin use has been found to improve the outcome of STEMI and is considered safe. 6,8 Patients who got aspirin during the first four hours after start of symptoms had a reduced death rate than those who received aspirin after five to eight hours. 9 Even after adjustment for potential confounders like gender, age, history of heart disease and medication, early use of aspirin remained independently correlated with smaller infarct size and non-Q wave.…”
Section: Introductionmentioning
confidence: 99%